Strategi Komunikasi Persuasif Pencegahan Bullying Pada Siswa Di Smk Pesantren Terpadu Mojokerto - Firdaus, Achmad (PT. Kreasi Karya Majakata, 2023)
Bullying behavior, which can also be called intimidating, involves attacking people physically, verbally, and psychologically by individuals or groups who are stronger than those who are weaker. In the school environment that is under the auspices of Islamic Boarding Schools, bullying is still encountered. This, of course, will have a negative impact on school activities for victims of bullying. Schools already have a strategy for handling bullying cases for their students in an effort to prevent acts of bullying, but the results are not efficient enough. So the researchers took the title Persuasive Communication Strategy for Prevention of Students’ Bullying at SMK Pesantren Terpadu Mojokerto. With the formulation of the problem under study, namely